Survey of bullous pemphigoid disease in northern Iran. (17th March 2015) - Banihashemi, Mahnaz; Zabolinejad, Naghmeh; Vahabi, Sadegh; Razavi, Hamed S.
Abstract Background Bullous pemphigoid is an autoimmune subepidermal blistering skin and mucous membrane disease that usually occurs in elderly people. This study was done to determine clinical features, paraclinical findings, incidence of mucosal lesions, prognosis, course of the disease, and mortality rate of patients with bullous pemphigoid. Method Retrospective descriptive study that reviews the existing files of 122 patients with bullous pemphigoid referred to dermatology clinics of Ghaem and Imam Reza hospitals in Mashhad, Iran, from 1995 to 2010. Result The majority of patients were aged between 60 and 79 years, and 53% of them were women. The major prodromal lesions were erythematous and urticarial (36.8%) and eczematous lesions (32.7%); 84.3% of patients complained of pruritus, and mucosal lesions were observed in 31.1% of patients (all in the oral mucosa). The most frequent concurrent diseases with pemphigoid were hypertension and diabetes mellitus. Conclusion Clinical features, paraclinical findings, incidence of mucosal lesions, prognosis, course of the disease, and mortality rate of bullous pemphigoid in the Khorasan region were approximately similar to results from other regions.